Anti-corruption upbringing as an important direction of activities by pedagogue- philosophers (Journal of Educational Sciences, 2017)
This article represents reflection about importance of carrying out by teachers of philosophy of work on anti-corruption education. The author appeals to a philosophy role in world outlook formation of the personality. Parallels with tasks of pedagogics and philosophy which were set by Socrates, al Farabi, E.Ilyenkov, V. Semenkov are drawn. The reference todata of sociological research is given. According to the research of the researсh center «Youth» of the L.N. Gumilev Eurasian national University from the 31 problems for young people actual inflation (in the first place) – inflation, the second is corruption. The author proposes to shape anticorruption ethical virtue. Instruments of formation may be an appeal to philosophy and books and education. Figuratively, allegorically, the authorcalls for the study of philosophy: «make friends with the philosophy that teaches us to see equally clearly how the roses and thorns of real life», «make friends with the philosophy which does not fade in the sunlight, and remembers about the dark clouds looming over the horizon of our age, and in the gloomy days of bad weather reminds us that storm clouds still concealed the clear and pure sky».
Keywords: philosophy; ethical virtue; counteraction of the corruption; world outlook